2008
DOI: 10.1042/bst0360416
|View full text |Cite
|
Sign up to set email alerts
|

The spindle position checkpoint: how to deal with spindle misalignment during asymmetric cell division in budding yeast

Abstract: During asymmetric cell division, spindle positioning is critical to ensure the unequal segregation of polarity factors and generate daughter cells with different sizes or fates. In budding yeast the boundary between mother and daughter cell resides at the bud neck, where cytokinesis takes place at the end of the cell cycle. Since budding and bud neck formation occur much earlier than bipolar spindle formation, spindle positioning is a finely regulated process. A surveillance device called the SPOC (spindle pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 58 publications
0
37
0
Order By: Relevance
“…Zarzov et al observed via electron microscopy specific defects in spindle pole body (SPB) duplication which could be corrected by the overexpression of the Hsp90-encoding gene HSP82, implying a role for this chaperone in maintaining SPB function during heat shock (525). SPB defects in these mutants are also consistent with the activation of the spindle pole checkpoint and the G 2 /M arrest point (136).…”
Section: Physiological and Metabolic Adaptationmentioning
confidence: 49%
“…Zarzov et al observed via electron microscopy specific defects in spindle pole body (SPB) duplication which could be corrected by the overexpression of the Hsp90-encoding gene HSP82, implying a role for this chaperone in maintaining SPB function during heat shock (525). SPB defects in these mutants are also consistent with the activation of the spindle pole checkpoint and the G 2 /M arrest point (136).…”
Section: Physiological and Metabolic Adaptationmentioning
confidence: 49%
“…Cells lacking cytoplasmic dynein (dyn1D cells) frequently misposition their spindles at low temperature and arrest in anaphase because the MEN GTPase Tem1 is inhibited by Bub2-Bfa1 (for review, see Fraschini et al 2008). When the GAP is inactivated by deleting BUB2 or BFA1, cells with mispositioned spindles will not arrest in anaphase, but rather exit mitosis to produce anucleate and multinucleate cells (Supplemental Fig.…”
Section: Lte1mentioning
confidence: 99%
“…The spindle position checkpoint (SPOC) is the important pathway that blocks mitotic exit and cytokinesis in case of mitotic spindle misalignment [32]. This pathway is crucial for budding yeast since the division site is determined early in the yeast cell cycle, in late G1 concomitantly with bud site selection, while the mitotic spindle is assembled after this event.…”
Section: The Complex Regulation Of the Protein Kinase Kin4 A Key Plamentioning
confidence: 99%